Keefektifan Bioinsektisida Berbasis Cendawan Entomopatogen Talaromyces pinophilus dan Minyak Nabati terhadap Hama Penggerek Buah Kopi - Khaerati Khaerati; Gusti Indriati; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
The coffee berry borer (CBB) Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae), is one of the main pests that cause yield losses in coffee plants. This pest directly attacks the coffee berries, both immature and ripe. The entomopathogenic fungi is one of the potential biological agents for CBB, environmentally friendly and does not kill non-target organisms. The study was conducted at the Integrated Laboratory, Industrial and Beverage Crop Research Institute, from June to October 2018. The aim of this study was to examine the effectiveness of bioinsecticide based on entomopathogenic fungus of Talaromyces pinophilus (EFTP) and vegetable oil on CBB. The completely randomized design with 31 treatments and 3 replications was used in this study. The 31th of treatments consisted of 9 formulas of bioinsecticide based on EFTP and vegetable oil, control-positive (bioinsecticide based on EFTP and water), and control- negative (Klorpirifos insecticide). Variables observed were the activities of EFTP enzyme, effectiveness of vegetable oil as a carrier material, mortality of CBB beetles, percentage of CBB attacks, percentage of hollow berries, and number of holes per 10 coffee berries. Results showed that the formula of bioinsecticide based on EFTP produce the chitinase and protease enzymes which were potential as biological agents to control CBB in vitro. Soybean oil is the most effective as a carrier material in formulating EFTP. The formula of S69MK30 and S79MK20 in concentration of 7.50% respectively have the highest potential as biological agents to control CBB. Other potential formula is S69MKT30 in concentration of 7.50%.